PROBLEMS WITH THE DISTANCE LEARNING SYSTEM IN LEARNING ENGLISH AT SMP NEGERI 2 TONDANO FOR GRADE 3C STUDENTS - Rivaldo Wales; Noldy Pelenkahu; Tirza Kumayas (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study aims to determine the problems that occur in the distance learning   system in learning English. This researh was conducted at SMP Negeri 2 Tondano. The method used in this research was qualitative method. Data collection in this study was questionnaire made in google form and distributed to 29 students. The results of this study conclude that online learning is carried out using media applications such as Whatsapp, Google meet, Google classroom and Zoom which are used when learning online at SMP Negeri 2 Tondano. There are obstacles for teachers in conducting online learning to students, including the lack of student understanding when carrying out the online learning process. This is because students do not understand the material given because they do not meet directly and the teacher is difficult to monitor student progress accurately. The main factor that is more important is the lack of facilities owned by students when studying online because not all students have facilities such as cellphones, laptops or computers as study equipment. Besides that, another factor is internet packages that are expensive and have a bad network in their environment.